ANALISIS KEKUATAN ALAT BUKTI SAKSI TESTIMONIUM DE AUDITU DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA KOTA MALANG - rohmat arif; Fathurrahman Alfa; Syamsu Madyan (Fakultas Agama Islam UNISMA, 2020)
A witness is a person who has met the formal and material requirements and his testimony is given in court from what he has seen and experienced by himself, but what if the witness does not see it directly but only hears it from someone else ? in the witness's civil law it is called testimonium de auditu. As for the problems of the statement above is as follows : How about the strength of the witness testimonium de auditu in the divorce case at Religious court in Malang city ? and How is the consideration of judges about the witness testimony de auditu at Religious court in Malang city ?. To answer the questions above, the researcher uses a qualitative approach, The data is collected using documentation interview techniques with three judges as informants, and library research about testimonium de auditu. From the results of the research that has been done it can be concluded that according to the judge, the strength of the witness testimony de auditu at the Religious Court in malang city is not recognized as a tool of evidence, but rather in practice The judge has the authority to examine the witness, and it is not wrong for the judge to hear the witness' testimony, The not as direct evidence. But the testimony can beoconstrued asoa tool of proof of hypothesis with objective and rational judgment and it can serve as a basis fot proving something. And the judge’s consideration of the use ofithe witness deiauditu inidivorceicases inireligious courts malang city. that is based on the article 16 (1) UU Number.14 year 1970 junco. UU Number.4 year 2004 about the main points of judicial authority, jurisprudence supreme court 11 november 1959 number. 308 K/SIP/1959. and This includes cese verstek so there is no objection. Keywords: divorce case, witness testimonium de auditu, religious courts